2015
DOI: 10.1007/s00425-015-2362-9
|View full text |Cite
|
Sign up to set email alerts
|

Tissue culture and associated biotechnological interventions for the improvement of coconut (Cocos nucifera L.): a review

Abstract: The present review discusses not only advances in coconut tissue culture and associated biotechnological interventions but also future research directions toward the resilience of this important palm crop. Coconut (Cocos nucifera L.) is commonly known as the 'tree of life'. Every component of the palm can be used to produce items of value and many can be converted into industrial products. Coconut cultivation faces a number of acute problems that reduce its productivity and competitiveness. These problems incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 103 publications
1
35
0
1
Order By: Relevance
“…This may have benefits for public acceptance. Finally, aside from the aforementioned challenges in genetic improvement of coconut, the production of seedlings on a large scale once resistance is identified is also difficult and slow, however improvements in tissue culture methods are showing promise that this process could be improved in the future (Nguyen et al, 2015). …”
Section: Disease Managementmentioning
confidence: 99%
“…This may have benefits for public acceptance. Finally, aside from the aforementioned challenges in genetic improvement of coconut, the production of seedlings on a large scale once resistance is identified is also difficult and slow, however improvements in tissue culture methods are showing promise that this process could be improved in the future (Nguyen et al, 2015). …”
Section: Disease Managementmentioning
confidence: 99%
“…This result supports the view that the makapuno genotype is preserved through in vitro embryo culture. However, the cultivation of the embryo culture-produced seedlings cannot guarantee the production of a trueto-type palm since a makapuno-bearing palm is presumably heterozygous [3]. Recent research using DNA-based markers has developed a way to identify planting material that is carrying the makapuno trait, by assessing visually its genetic make-up in the young [23] and mature palms (53).…”
Section: Planting Managementmentioning
confidence: 99%
“…[2]. In addition, the field cultivation of coconut in some regions has been seriously threatened by a wide variety of biotic and abiotic factors, including lethal diseases and pests, and natural calamities [3]. The major era of establishment of coconut plantations for export of copra and oil was the period of its very high price, between the years 1900 and 1930.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the feasibility of the vitrification technique for the cryopreservation of BGD zygotic embryos (LEDO et al, 2018). Moreover, regeneration techniques by somatic embryogenesis from plumules are more interesting from the point of view of breeding and conservation of genetic resources because they allow obtaining higher number of plants (NGUYEN et al, 2015).…”
Section: Introductionmentioning
confidence: 99%